How Does AI Support Neurosurgical Procedures? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2017)
Artificial intelligence (AI) is rapidly transforming various fields, and medicine is no exception. In the highly specialized field of neurosurgery, AI is eme...
Keywords: AI in Surgery and Robotics; Support; Neurosurgical; Procedures; Artificial Intelligence; Machine Learning; Diagnostics